2019
DOI: 10.3390/s19235193
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Device for the Knee Monitoring of Orthopaedic Patients

Abstract: Fast-track surgery is becoming increasingly popular, whereas the monitoring of postoperative rehabilitation remains a matter of considerable debate. The aim of this study was to validate a newly developed wearable system intended to monitor knee function and mobility. A sensor system with a nine-degree-of-freedom (DOF) inertial measurement unit (IMU) was developed. Thirteen healthy volunteers performed five 10-meter walking trials with simultaneous sensor and motion capture data collection. The obtained kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…Besides objective activity monitoring, Hospital Fit also provides patients insight into their recovery progress and offers physiotherapists the option of creating a patient-specific exercise program supported by videos. Recently, an increasing number of other mHealth tools have been investigated within the orthopedic rehabilitation pathway [28][29][30][63][64][65][66][67][68][69]. These tools are predominantly prescribed in support of outpatient physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides objective activity monitoring, Hospital Fit also provides patients insight into their recovery progress and offers physiotherapists the option of creating a patient-specific exercise program supported by videos. Recently, an increasing number of other mHealth tools have been investigated within the orthopedic rehabilitation pathway [28][29][30][63][64][65][66][67][68][69]. These tools are predominantly prescribed in support of outpatient physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Example of a video consultation with inspection of the knee joint consultation, therefore, has its limitations in the diagnosis of instabilities of the knee joint as well as shoulder diseases [2,7,32]. Perhaps new methods using the modern sensors can improve the possibilities for telemedicine for these areas in the future [17]. For example, a recent study showed that motion-based machine learning software has the potential to replace an examination knee within 5° after goniometer measurements remotely [29].…”
Section: Diagnostic Video Consultationsmentioning
confidence: 99%
“…For example, a recent study showed that motion-based machine learning software has the potential to replace an examination knee within 5° after goniometer measurements remotely [29]. In the future, functional diagnostics over distances can also be possible on the knee with help of sensors [17,29].…”
Section: Diagnostic Video Consultationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The department is currently experimenting with knee sleeves that can be used to monitor postoperative range of motion remotely, providing surgeons with real-time information on the activity level and progress of patients. 48,49 ERAS for knee arthroplasty does not seem to be affected by the pandemic. In fact, the acceptance seems to be enhanced by it.…”
Section: Teleconsultation Services and Medication Deliverymentioning
confidence: 99%